Efficacy of Antiemetic Regimens for Prevention and Treatment of Chemotherapy-Induced Nausea and Vomiting in Patients of Breast Cancer Receiving Highly Emetogenic Chemotherapy - Vij, Soumya; Dhasmana, Dilip Chander; Bala, Suman; Verma, Sanjiv Kumar (Indian Journal of Medical and Paediatric Oncology, 2020)
Background: Chemotherapy is fraught with serious and troublesome adverse effects, of which nausea and vomiting appears earliest and is the most disturbing. Therefore, this study was planned to investigate the antiemetic drug regimens used for chemotherapy-induced nausea vomiting (CINV) in patients with breast cancer receiving highly emetogenic chemotherapy (HEC). Subjects and Methods: An observational follow-up study was conducted to assess the efficacy of antiemetic regimens in breast cancer patients receiving HEC. A total of 71 newly diagnosed patients with breast cancer were included in the study. Patients were assessed for nausea by the visual analog scale, and a history of emetic episodes and need for rescue medication were recorded at 0 h, 6 h, 24 h, 48 h, and 120 h post-chemotherapy till three cycles. Results: The patients were prescribed a combination of ondansetron and dexamethasone (n = 23, n = 17, and n = 13 in first, second, and third cycle, respectively) or a combination of aprepitant, ondansetron, and dexamethasone (n = 48, n = 54 and n = 56 in the first, second, and third cycle, respectively). The intensity of nausea was higher for the patients who were prescribed ondansetron and dexamethasone regimen as compared to patients prescribed aprepitant additionally. Complete response, i.e., no emesis and no rescue medication, was higher in triple-drug regimen (52% vs. 0.4%, 63% vs. 17.6%, and 69% vs. 23% in three cycles, respectively). Conclusion: The control of CINV was better with a combination of aprepitant, ondansetron, and dexamethasone as compared to a regimen without aprepitant.
Keywords: 5-HT3 receptor antagonist; breast cancer; chemotherapy-induced nausea and vomiting; highly emetogenic chemotherapy; NK-1 receptor antagonist